Aspectos da biologia reprodutiva de Dendropsophus haddadi (Anura: Hylidae) e a influência dos locais de oviposição no dimorfismo sexual e fecundidade em anuros - Silva, Nelson Rodrigues da (2020)
Anuran amphibians exhibit a great diversity of reproductive modes. The behaviors of laying eggs in the water or on terrestrial habitats involve different adaptations and terrestriality evolved independently in the group. Morphological differences between males and females and female fecundity are important traits related to the reproductive modes. However, basic information on biology is not available for many species, hampering studies on ecology and evolution of anurans. Thus, the aims of this thesis were to study the biology of one species with arboreal reproductive mode and investigate the interplay among arboreal modes, fecundity and sexual dimorphism in anurans. In the first chapter, we describe the reproductive biology of Dendropsophus haddadi, a species endemic to the Atlantic forest. Two populations were studied in Maceió, Alagoas state, northeastern Brazil. Individuals were observed perched on the vegetation, approximately 3-5 m high, at the margins of temporary water bodies. Males were territorial, emitted calls, visual signs, and engaged in fights. Clutches were found on trunks, leaves and twigs above the water. Number of eggs was positively correlated with clutch size and our observations suggest that, in the absence of rains, females may protect the eggs against desiccation by joining them right after oviposition. This form of parental care is a novelty for the genus. Sexual size dimorphism (SSD) results from natural and sexual selection pressures on both sexes and fecundity is an important selective pressure on female size. Thus, in the second chapter, we investigated the influence of the oviposition site on SSD and female fecundity in Anura and in the Hylidae family. We analyzed 385 anuran species (32 families) exhibiting aquatic (271), arboreal (48), terrestrail hidden (35), and terrestrail exposed (31) clutches. For Hylidae, we analyzed 221 species with aquatic (175), arboreal (30) and hidden (16) clutches. Mean SSD did not vary among species with different oviposition sites; in general, males were ca. 20% smaller than females, what could be related to cloacal juxtaposition and fertilization success. Nonetheless, in species with hidden clutches, males and females tended to have similar body sizes, what could be explained by restrictions to female size increase because of space limitation to amplectant pairs. We also tested the hypothesis that females with arboreal clutches may suffer restrictions to fecundity increase to offset the costs of carrying amplectan males. In general, fecundity was smaller in arboreal breeders compared to that of aquatic breeders. However, in hylids, fecundity tended to be smaller in arboreal breeders compared to all other oviposition sites, what suggests that arboreality may restrict female fecundity increase. Our findings for Anura and Hylidae showed the complex relationship among oviposition site, fecundity and SSD in frogs, suggesting that the reproductive microhabitat may also influence female size and fecundity. Thus, degree and direction of SSD in anurans may result from complex mechanisms operating at different evolutionary scales.